Simple-DF versus selective-DF relaying over Rayleigh turbulence-induced FSO fading channels - Abou-Rjeily, Chadi (2017)
In this paper, we consider the problem of relay-assisted free-space optical (FSO) transmissions. We evaluate the diversity orders that can be achieved by simple-DF and selective-DF relaying protocols over quantum-limited FSO systems that are subject to Rayleigh fading. We prove that for a Nr-relay system, selective-DF captures the full spatial diversity order of Nr +1 while simple-DF achieves a reduced order of ⌈Nr/2⌉+1 making this scheme highly suboptimal for FSO communications.